Knowledge translation initiatives at the Transitional Pain Service: insights from healthcare provider outreach and patient education - Anna M. Lomanowska; Rabia Tahir; Christina Choo; Sabrina Zhu; Dora Y. Wang; P. Maxwell Slepian; Joel Katz; Hance Clarke (BMC Health Services Research)
Abstract Evidence-based treatment of chronic pain requires a multidisciplinary approach grounded in the biopsychosocial model. Implementing this approach within health systems relies on its acceptance by both healthcare providers and patients. While pioneering multidisciplinary pain clinics can serve as a model for implementation, a systematic effort is needed to share knowledge effectively and broadly. In the current paper we provide an overview of the knowledge translation initiatives undertaken at our Transitional Pain Service (TPS) at Toronto General Hospital, a state-of-the-art multidisciplinary pain program established in 2014 for patients at risk of developing chronic pain after surgery. The TPS team strives to enhance acceptance of this model of care among patients and providers, facilitate the establishment of similar clinics, and promote patient understanding of the integrated multidisciplinary pain care approach. Guided by the Knowledge to Action (KTA) framework, knowledge translation activities undertaken by our TPS team include clinician training, resources and outreach activities for providers, and patient education. Resource development was preceded by consultation and needs assessment among patients and providers and feedback from both groups was incorporated as part of the development process. The tailored resources were disseminated via the TPS clinic website and monitoring of online usage enables continuous evaluation of engagement. Barriers to engagement with the resources were examined through patient surveys and staff interviews. Based on these activities, we offer insights gained by our team throughout the knowledge translation process and provide recommendations for other clinical teams who wish to undertake similar initiatives.